The evolution of systemic therapy in sarcoma. Issue 2 (February 2013) - Constantinidou, Anastasia; Pollack, Seth; Loggers, Elizabeth; Rodler, Eve; Jones, Robin L
Approximately 50% of patients with localized soft tissue sarcomas will develop recurrent disease after complete surgical resection, requiring alternative means of treatment. Conventional chemotherapy comprising of doxorubicin and ifosfamide has shown benefit in advanced disease, however, there remains a clear need for more effective, less toxic, therapies for the treatment of this heterogeneous group of mesenchymal malignancies. Recently, greater emphasis has been placed on the underlying biology of individual sarcoma subtypes, with the development and evaluation of novel therapies both in common and in rare subtypes. In addition, there is a greater specificity in the selection of chemotherapy agents based on activity in individual histological subtypes. Despite these advances the management of sarcoma, and in particular of rare subtypes, remains a major challenge. Some histological subtypes are resistant to conventional chemotherapy and patients with these diseases should be offered participation in early phase clinical trials of novel drugs.